Antioxidants: The counterstriking immunomodulators in therapeutics of oral lesions - Krishna Takkella, Bharani; Sirisha, Mulagolla; Ram Sunil, Chukka; Polepalle, Tejaswin; MadhuKiran Naik, Katravath; Krishna Thakkella, Chaitanya; Sujana, Varri; Sri Sai Kandi, Bhavya (Trends in Immunotherapy, 2022)
Antioxidants are a group of natural phytochemicals found in dietary ingredients that can be utilised to treat oral lesions and diseases. They are employed as chemical compound alternatives since they have less adverse effects. The dietary antioxidants found in fruits and vegetables reduce the damage by modulating detoxification enzymes, increasing immune system, and hormone metabolism. Scientists were drawn to antioxidants because of their ability to modify cell cycle controls, apoptosis, invasion, angiogenesis, and metastasis. They have demonstrated significant success as single treatments or in combination with chemo-preventive medicines for oral lesions. Inside this article, we will look at the immuno-modulating effects of antioxidants, which aid in the treatments and even sometimes avoidance of numerous oral and maxillofacial conditions that contribute to morbidity, such as autoimmune lesions, and death, such as oral cancer. Antioxidants are chemicals that considerably impede or decrease the degradation of a living matter and defend the organism from oxidative harm. As a result, the sickness will be significantly reduced.